Development of Tolerance Attitude Assessment Instruments on Learning PPKn Based Android - Triyono, Triyono; Sunarto, Sunarto; Lestari, Wahyu (Universitas Negeri Semarang, 2019)
Needs analysis in developing tolerance attitude assessment instruments on Android-based PPKn learning is carried out with the aim of identifying teacher needs about tolerance attitude assessment instruments in the form of manuals and Android applications. The problem found by researchers is the assessment of tolerance in PPKn learning has not been implemented. At the time of observation it was found that there were no attitude assessment sheets and assessment rubrics in the Learning Implementation Plan (RPP). The results of the interview stated that teachers had difficulty in making attitude assessment instruments so that teachers needed the development of tolerance attitude assessment instruments on learning PPKn based Android. Android application made with simple codding. The research method used is research and development (R&D). Qualitative data analysis is used to describe triangulation of data sources, while quantitative data analysis is used to test validity, reliability and practicality. The results of the needs analysis of 20 statement items filled by fifth grade elementary school teachers in Pabelan District amounted to 8 teachers obtained validity, each statement item is greater than rtable, 0.707 and is declared valid. Reliability obtained 0.973 and declared reliable. Guidebooks and Android applications that can be accessed through Google Drive and Play Store can be used by teachers to assess student tolerance. The practicality of a guidebook is done after the assessment instruments are valid and reliable. Teachers can use the instrument of tolerance attitude assessment books on learning of PPKn based Android in classroom learning.